Cobalt-doped g-C3N4/MOF heterojunction composite with tunable band structures for photocatalysis aerobic oxidation of benzyl alcohol. (1st April 2022) - Amini, Ali; Karimi, Meghdad; Rabbani, Mahboubeh; Safarifard, Vahid
Graphical abstract: Abstract: Due to decrease environmental pollution and energy crisis, it is necessary to find an excellent solution to utilize visible light with photocatalyst technology. Therefore, it can be argued that the use of photocatalysts as well as clean and natural solar energy can be considered as an efficient and promising solution. Constructing heterostructure photocatalysts with metal-organic frameworks (MOFs), and graphitic carbon nitride (g-C3 N4 -Co) is a powerful viewpoint to obtain high performance in visible-light photocatalysis. In this work, we prepared a heterostructure photocatalyst using Zn-based MOF and cobalt-doped graphitic carbon nitride (g-C3 N4 -Co) termed TMU-22/g-C3 N4 -Co. Characterization of TMU-22/g-C3 N4 -Co composite was performed by PXRD, FT-IR, TGA, SEM, EDS, UV-vis DRS, and BET. This composite showed a high performance in aerobic oxidation of benzyl alcohol to benzaldehyde under visible-light irradiation in mild conditions (at atmospheric pressure and room temperature) which comes from the cooperative performance of g-C3 N4 -Co and TMU-22(Zn) components. Additionally, studies performed using radical scavengers indicated that electrons and holes serve as the main reactive species. The superior photocatalytic activity of the composite is attributed to the enhanced separation of the photogenerated electron-hole pairs, as well as increased visible-light absorption.